2014
DOI: 10.1161/jaha.113.000622
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Krüppel‐Like Factor 4 in Endothelial and Hematopoietic Cells Enhances Neointimal Formation Following Vascular Injury

Abstract: BackgroundKrüppel‐like factor 4 (Klf4) is involved in a variety of cellular functions by activating or repressing the transcription of multiple genes. Results of previous studies showed that tamoxifen‐inducible global deletion of the Klf4 gene in mice accelerated neointimal formation following vascular injury, in part via enhanced proliferation of smooth muscle cells (SMCs). Because Klf4 is also expressed in non‐SMCs including endothelial cells (ECs), we determined if Tie2 promoter‐dependent deletion of Klf4 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 33 publications
0
59
1
Order By: Relevance
“…27,28 Second, we previously reported that the number of neutrophils, lymphocytes, and monocytes in the blood did not differ between the Klf4 cKO and control mice. 11 In this study we showed that the accumulation of neutrophils and lymphocytes was enhanced in the kidneys at 24 hours after I/R injury in Klf4 cKO mice compared with that in control mice. However, these inflammatory cells do not express endogenous Klf4 in either Klf4 cKO or control mice.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…27,28 Second, we previously reported that the number of neutrophils, lymphocytes, and monocytes in the blood did not differ between the Klf4 cKO and control mice. 11 In this study we showed that the accumulation of neutrophils and lymphocytes was enhanced in the kidneys at 24 hours after I/R injury in Klf4 cKO mice compared with that in control mice. However, these inflammatory cells do not express endogenous Klf4 in either Klf4 cKO or control mice.…”
Section: Discussionmentioning
confidence: 54%
“…11 Coimmunoprecipitation assays demonstrated that KLF4 and p65 physically interacted with each other. 11,33 In addition, we showed that TNFmediated increases in p65 binding to the VCAM1 promoter were attenuated in the presence of KLF4, as determined by chromatin immunoprecipitation assays.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations